Switch to maraviroc/raltegravir dual therapy leads to an unfavorable immune profile with low-level HIV viremia. (24th April 2015) - Campillo-Gimenez, Laure; Assoumou, Lambert; Valantin, Marc-Antoine; Pajanirassa, Priyadharshini; Villemonteix, Juliette; Soulié, Cathia; Marcelin, Anne-Geneviève; Costagliola, Dominique; Capeau, Jacqueline; Autran, Brigitte; Katlama, Christine; Guihot, Amélie
Abstract : Immunovirological consequences of a switch to a maraviroc/raltegravir dual therapy were analyzed in 16 HIV-infected patients with persistent viral load below 50 copies/ml. At 26-week postswitch, the CD4 + /CD8 + ratio decreased and the CD8 + T-cell activation increased. A decrease in classical monocytes was associated with a shift toward a proinflammatory monocyte profile and negatively correlated with ultrasensitive viral load. Thus, this therapeutic switch induced a proinflammatory profile probably driven by a slight loss of virus control.